Esbâbü Vürüdü’l-Hadis ve İbn Hibbân’ın Sahih’ninde Sebebe-i Vürüd ile ilgili verdiği bilgilerin incelemesi - Nassan, Musa (My University, 2021)
Hz. Peygamber’in sözlerinin, fiillerinin ve ikrarlarının sebebini araştıran Sebeb-i Vürûd ilmi, ulûm-u hadîs’in bir alt dalı olarak gelişmiştir. Bu hususta müstakil kitapların ortaya çıkması hicrî V. asra kadar gecikmişse de ilk dönem muhaddislerinden itibaren, ulemanın zihinde sebeb-i vürûd konusunun bulunduğu söylenebilir. Sebeb-i Vürûd’un ulûm-u hadis içerisinde kendisine bir yer edinme sürecinin Ezdî ile tamamlandığı sonrasında Ukberî ile devam ettirildiği anlaşılmaktadır. IV. yüzyıl muhaddislerinden olan ve sebeb-i vürûd’u hadis başlıklarında açıkça yazan ilk muhaddislerden birisi olan İbn Hibban’ın bu hususta onlara öncülük ettiğini tespit edebiliriz. İbn Hibbân’ın Sahih’inde sebeb-i vürûdu, “hadisin zikrediliş sebebi” ifadesiyle sunduğu ve “sebeb-i vürûd” kelimesini kullanmadığı görülmektedir. Bu durum onun döneminde “sebeb-i vürûd” teriminin muhaddisler arasında henüz sistemli olarak kullanılmadığı düşüncesini doğurmaktadır. İbn hibban, bâb başlıklarında “hadisin söyleniş illeti” ifadesini de kullanmaktadır. Ancak bu ikinci ifadesi, eserlerinde sebeb-i vürûd olarak zikredilmez. Nitekim bazı hadisleri aktarırken hem “hadisin zikrediliş sebebi”nden hem de “hadisin söyleniş illeti”nden ayrı ayrı bahsetmektedir.İbn Hibbân’ın, bir hadisin sebeb-i vürûdu varsa bunu Sahih’inde belirtmeye gayret ettiği anlaşılmaktadır. Bununla beraber eserlerinde geçen bazı hadislerin, sebeb-i vürûdu olmasına rağmen İbn Hibbân tarafından dile getirilmediğini tespit ettik. Benzer bir şekilde İbn Hibbân tarafından sebeb-i vürûd olarak belirtilmiş bazı hadislerin aslında sebeb-i vürûd olmadığı, îrad veya illet olduğu kaydedilebilir.

The science of Asbab al-Wurud, which examines the reason for the Prophet Muhammad’s (pbuh) sayings, deeds and approvals, has developed as a sub-field of Hadith studies. Although the emergence of distinctive books on this subject has been delayed until the 5th century AH, it can be said that the matter of Asbab al-Wurud was in the mind of the ulama since the first period Hadith scholars.It is understood that the process of finding a place for Asbab al-Wurud within the Hadith studies has been completed with Ezdi and continued with Ukberi. We can determine that, Ibn Hibban, who is one of the Hadith scholars (muhaddis) of 4th century AH and who is clearly write Asbab al-Wurud in the Hadith titles, was a pioneer for them on this matter.It is seen from Ibn Hibban’s Sahih that, he did not use the ‘Asbab al-Wurud’ term but instead he reflected ‘Asbab al-Wurud’ by the statement of ‘the reason why hadith is mentioned’. This situation raises the idea that the term ‘Asbab al-Wurud’ has not been used systematically among Hadith scholars in his time yet. Ibn Hibban has also used statement of ‘the causality of narration of hadith’. However, this second statement was not mentioned as ‘Asbab al-Wurud’ within his works. Hence, while narrating some of the hadiths, he refers both ‘the reason why hadith is mentioned’ and ‘the causality of narration of hadith’ separately. It is understood that Ibn Hibban has tried to indicate the Asbab al-Wurud for a hadith, if any, in his Sahih. However, we have determined that even though some of the hadiths have Asbab al-Wurud, it was not mentioned by Ibn Hibban. Similarly, it can be noted that some hadiths that are stated as Asbab al-Wurud by Ibn Hibban are not actually an Asbab al-Wurud, but instead Irad al-Hadith or Illiyet (Causality).
Keywords: : Hadis; Al-Bayan Ve't Tar'f Ibn Hamza; Al-Luma Suyuti; Asbab-as Erad; Esbâbü’l-irad; Esbâbü’l-Vürûd; Hadis; Hadith; Hidden Defects; Islam; İbn Hibbân; İllet Asbab-al Wurud; İslam; Sahih Ibn Hibban; Sahîh-i İbn Hibbân